Maternal Serum Uric Acid as an Index of Perinatal Outcomes in Severe Preeclampsia - Yassin Khalil, Rozhan; Saber Muhammed, Awat (Kurdistan Journal of Applied Research, 2018)
Preeclampsia is a multisystem disorder characterized by gestational hypertension after the 20th week of gestation with proteinuria, is common and dangerous adverse event of pregnancy. Several studies reported relationship between uric acid concentrations and severity of disease in pregnant women. The objective of this study was to explore the relation between serum uric acid level and perinatal outcomes. A case–control study conducted in Sulaimani Maternity Teaching Hospital from January 2014 to July 2014. Included 100 pregnant women in third trimester with signs and symptoms of labour, who had no comorbid diseases. Grouped to 30 control without hypertension, 30 with pregnancy induced hypertension (PIH) and 40 with severe preeclampsia based on clinical and laboratory evaluation. SPSS v21 was used for obtain mean, standard deviation, frequency and percentage. One way ANOVA test used to obtain P value with consider <0.05 significant value. Results show serum uric acid mean and standard deviation (±SD) for control, PIH and severe preeclampsia groups were (5.83 ± 9.544), (4.35 ± 1.372) and (7.59 ± 0.508) respectively. The positive and significant (? 0.001) correlation coefficient was found between high serum uric acid level and oligohydramnios, low birth weight and low Apgar score. The highest level of serum uric acid was recorded in preeclampsia group and the lowest level was in PIH group. Significant and adverse perinatal outcomes relation were noted in the patients with high serum uric acid (>7 mg/dl); decreased amniotic fluid index (AFI), caused low birth weight and low Apgar score. In conclusion that severity of illness in pregnant preeclampsia cases can be estimated by serum uric acid level and high serum uric acid indicate high risk cases. Maternal serum uric acid is a useful index for estimate fetal health status and predict neonate outcomes.